(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Tooth, due to the anatomical framework of hard minerals, is a reliable source in forensic identification, sex determination, and age estimation. Although Morphological, radiological, and histological methods are effective methods, the advancements in molecular methods have shifted the focus of research towards changes occurring in DNA to age and sex. Molecular methods are useful when other methods fail to estimate the age. Telomere length attrition and DNA methylation are the two extensively studied areas in dental forensic age estimation. This review attempts to narrate the current